Biaya Pendidikan, Motivasi, dan Minat Mahasiswa Mengikuti PPAk di Masa Pandemi Covid-19 - Geymina, Intan Nanda; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2024)
In the era of globalization, professional education is very necessary, especially for the younger generation who will compete with foreign workers as a result of the existence of the Asean Economic Community (AEC), which causes competition to become increasingly fierce. Various things can be done to improve one's quality, one of which is by taking Professional Accounting Education as an effort to produce professional accountant graduates by standardizing the quality of accountants in Indonesia. The aim of this research is to obtain empirical evidence of the influence of education costs, economic motivation and social motivation on students' intentions to take accounting professional education. The population of this research is all 235 accounting study program students at the Faculty of Economics and Business, Udayana University Class of 2018. Samples were collected using probability sampling techniques. The total sample was 148 people. Data was collected using a questionnaire. Multiple linear regression analysis was used to analyze research data. The findings show that educational costs, economic motivation and social motivation have a positive influence on students' intentions to pursue Accounting Professional Education. Keywords:Education Costs; Economic Motivation; Social Motivation; Student Interest